The Use of Economy Token to Reduce Tantrum Among Autistic Students - Mohamad Kassim Mohamed Yaseen; Mohd Mokhtar Tahar (Department of Special Education, 2018)
Token economy is one form of behavior modification in addressing the behavior problem among special education students. This study aims to see the effectiveness of using token economy in reducing the behavior of autism students. This study focuses on an autism student that studying in one of the primary school in Sentul District of Kuala Lumpur. The study uses the A-B-A Model design which encompasses three phases, baseline phase (A) observation of the behavior of the subject subject to the predetermined time. The intervention phase (B), the implementation of economic and phase token without intervention (A), is a phase without the application of token economy. Data were collected through observation on frequency of behavior of the study subject. The observation was conducted for 6 weeks involving three timelines of the study ie before, during and after intervention. Data obtained were analyzed by using descriptive statistic. Data then illustrated through frequency tables and line graphs to show the effectiveness of the economic token interventions implemented. The findings show that the use of token economy reduces the behavior of autism students. Future research can use the finding from this study as a guideline for special education teachers in addressing the problem of special needs students. In regard to this study, it will be a source of inspiration to the teacher that negative behavior can be changed when correct methods and technique are implemented.